Aflatoxin induced cytological alternations in ducks - Vigil Anbiah S (Department of Pathology, College of Veterinary and Animal Sciences, 1996)
An experiment study was conducted in desi ducks to assess the cytological alterations induced by aflatoxin BI (AFBI) and 4 dimethyl amino azo benzene (4 DAB). One hundred and eight desi ducks of one month age were selected for the study. The birds were divided into two treatment groups which were given AFBI (10 µg/kg body weight and 15µg/kg body weight) and 4 DAB (5 mg and 10 mg/kg body weight) and a control group. Each group consisted of thirty six birds. Body weight, haemogram, clotting time, total serum protein, serum albumin, serum globulin, albumin – globulin ratio, serum aspartate amino transferase, serum alanine amino transferase, serum bilirubin and cytogenetic assay were estimated at periodic intervals. The ducks were subjected to detailed autopsy and histopathology. Clinically, the experimental birds were healthy. Anaemia, leucocytosis and increased blood clotting time were noticed in birds which received 15µg/kg body weight of AFBI and both the dose levels of 4 DAB. Total serum protein was reduced in all the treated birds. In the aflatoxin group, serum albumin and globulin levels were decreased. Albumin – globlin ratio was increased in 4 DAB treated birds. Serum aspartate amino transferase level was elevated in birds which received 10µg/kg body weight of AFBI and 10 mg/kg body weight of 4 DAB. Birds which received AFBI as well as 10 mg/kg body weight of 4 DAB showed an elevation in serum alanine amino transferase level. Serum bilirubin was increased in all the treated birds. Those ducks which were fed with AFBI at 15µg/kg body weight showed tendency of hepatoma formation during the experiment. The ducks which received 5 mg/kg body weight of 4 DAB exhibited gross and histopathological lesions suggestive of hepatosis and mild cirrhosis. The birds given 10 mg/kg body weight of 4 DAB revealed gross as well as histopathological lesions of hepatic degeneration and necrosis and indications of neoplatic changes. Trend towards polyploidy was the major chromosomal aberration observed in ducks which received 15µg/kg body weight of AFBI.